Apparent soil electrical conductivity in two different soil types - Nunes Medeiros, Wilker; Magalhães Valente, Domingos Sárvio; Marçal de Queiroz, Daniel; de Carvalho Pinto, Francisco de Assis; Rodrigues de Assis, Igor (Revista Ciência Agronômica, 2023)
Mapping the apparent soil electrical conductivity (ECa) has become important for the characterization of thesoil variability in precision agriculture systems. Could the ECa be used to locate the soil sampling points for mapping thechemical and physical soil attributes? The objective of this work was to examine the relations between ECa and soil attributesin two fields presenting different soil textures. In each field, 50 sampling points were chosen using a path that presented a highvariability of ECa obtained from a preliminary ECa map. At each sampling point, the ECa was measured in soil depths of 0-20, 0-40 and 0-60 cm. In addition, at each point, soil samples were collected for the determination of physical and chemical attributesin the laboratory. The ECa data obtained for different soil depths was very similar. A large number of significant correlationsbetween ECa and the soil attributes were found. In the sandy clay loam texture field there was no correlation between ECa andorganic matter or between ECa and soil clay and sand content. However, a significant positive correlation was shown for theremaining phosphorus. In the sandy loam texture field the ECa had a significant positive correlation with clay content and asignificant negative correlation with sand content. The results suggest that the mapping of apparent soil electrical conductivitydoes not replace traditional soil sampling, however, it can be used as information to delimit regions in a field that have similarsoil attributes.